Aktivitas Amilolitik Bakteri Sedimen Mangrove Pantai Logending, Ayah, Kebumen pada Suhu dan pH Berbeda - Alfiani Rahmawati; Oedjijono .; Dini Ryandini (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The main purpose of this study wereto determine the ability of mangrove sediment bacterial isolates to produce amylase, to determine the optimum pH and temperature on the amylase activity, and to identify theamylase-producing bacteria. The research was conducted by survey method. The research stages included, screening of amylolytic bacteria, growth curvespreparation, amylase production, optimizing amylolytic activity at varies oftemperature (35ºC; 36ºC; 37ºC; 38ºC) and pH (4.5; 5; 5.5; 6) and characterization of amylolytic isolates. Parameters measured were amylolytic index, amylase enzyme activity unit, total bacterial unit, and identity of amylolytic bacteria from mangrove sediments. Data analysis was done descriptively. The results showed that the highest amylolytic index were shown by isolate LG113 with an amylolytic index value of 9,86 mm from 10 amylolytic isolates from mangrove sediments. The optimum temperature of amylase activity was 37ºC(2,13 U/mL) and the optimum pH was 6(2,14 U/mL). The total number of amylolytic bacterial cells at the end of production time was 1,94x1013 CFU/mL. The identity of isolates of amylolytic bacteria from mangrove sediments at the Logending beachwas belong toBacillus genus.